Childfree dalam Perkawinan: Tinjauan Kritis dalam Perspektif Maqashid Syariah - Alqusni , Toriq; Nurjanah, Siti; Siradjudin, Azmi (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
The phenomenon of childfree marriage has become an important issue in social and religious discourse, particularly in the context of Islam. This study examines the concept of childfree marriage from the perspective of Maqashid Syariah, focusing on hifz an-nasl (protection of lineage) and the concept of maslahah (benefit) in Islamic law. The findings indicate that childfree has developed as a social phenomenon influenced by various cultural and individual factors. From the perspective of Maqashid Syariah, having children is classified as dharuriyyat (a fundamental necessity) to ensure the continuity of future generations. The decision to be childfree in marriage may be justified if it is based on maslahah dharuriyyat, such as health risks or difficult social conditions. However, if the decision is solely driven by hajiyat or tahsiniyat considerations, such as career priorities, personal freedom, or concerns about physical appearance, it may conflict with Islamic legal objectives. This study also identifies three main factors influencing the decision to be childfree in marriage. First, medical and mental health factors, including maternal health risks, psychological disorders, and past trauma, which relate to hifz an-nafs (protection of life). Second, economic factors, such as financial instability and high living costs, which are linked to hifz al-maal (protection of wealth). Third, personal factors, including career ambitions, lifestyle preferences, and beauty standards, which influence hifz al-din (protection of religion) and hifz al-aql (protection of intellect). Therefore, the decision to be childfree in marriage is not merely a personal preference but must also be evaluated within the framework of Maqashid Syariah to ensure alignment with Islamic values. This study suggests further research on the social and religious implications of this phenomenon and encourages scholars and academics to provide legal and ethical guidance for couples considering a childfree marriage.